Ravish the Republic: The Archives of The Iron Garters Crime/Art Collective. (punctum books, 2015)
In the 2011 book Dark Matter: Art and Politics in the Age of Enterprise Culture, the artist Gregory Sholette posits that we are living in an era of surplus creative energies concentrated in a teeming archive of artists, the poor, the "unskilled" and the "economically invisible." It is a potentially disruptive archive that capitalism can't always manage but can still hope to eventually exploit and assimilate. Within this archive seethes creative energy that can extend itself in unique and unsettling ways, across multiple categories and disciplines. Often, however such energy is captured by the winners and arbiters in our "risk society" and thereby sanitized and neutralized. So it becomes necessary for artists, theorists, writers and activists to be versatile in their tactics, cryptic and evasive in their manifestations and criminally implacable in their visions. The Iron Garters are an "art gang" that masquerades, disseminates and performs as your archetypal "criminals," "outcasts" "mystics," "losers" and "lunatics": in short, a vital and necessary social surplus. Their antics have been traced back to Jean Genet's novel The Thief's Journal, the films of Kenneth Anger, as well as the Dada poems of Baroness Elsa and Hugo Ball. Yet still other Garters have been nourished on the Vienna Actionists, Genesis P-Orridge, Diamanda Galas, Gilles Deleuze, Samuel Delany, and the dulcet sounds of The Cramps. With a critical and aesthetic arsenal salvaged from underground "kulchurs" and academia's collective libido, the Iron Garters are not afraid to demand excitement along with analysis, frenzy coupled to resistance, and fashion inseparable from infiltration. Founded in San Francisco on a full moon night after a "deathpunk" show, the original members grew adversely impacted by the economic invasions reducing a once great city to a tepid monoculture. Fueled by queer, antinomian, heretical and radical traditions, the Garters pilgrimaged into various trans-continental sanctuaries and beachheads, leaving behind them radiant paper trails of provocation and sedition. This volume is one such radiant paper trail.